(untitled) (Swiss Medical Weekly, 2018)
Hepatitis C is a potentially fatal viral infection that mainly affects vulnerable patient groups. Given the high efficacy of the new direct-acting antivirals (DAAs), the World Health Organization (WHO) aims to eliminate viral hepatitis as a global health threat by 2030. However, due to the high cost of DAAs, this recommendation has put significant pressure on the budgets of countries with mandatory health insurance, such as Switzerland. There are particular challenges related to populations with low socioeconomic status or without residence permits who might not be covered by health insurance, or who forgo health care for economic reasons. This article discusses some of the key issues on this topic, such as reaching the populations most at risk from the hepatitis C virus (HCV) infection, and improving access to care and treatment for underserved, uninsured populations. We suggest a personal importation scheme for unapproved generics of DAA medications, and the use of a buyers’ club as a strategy for improving universal access to hepatitis C medicines among vulnerable populations such as uninsured patients, in order to achieve the WHO goals with minimal disruption of the conventional, patent-based business model.